Resilience among parents whose child died of cancer – investigating its role on psychological distress and prolonged grief disorder: results from a cross-sectional survey in Switzerland - Peter Francis Raguindin; Eva De Clercq; Anna Katharina Vokinger; Eddy Carolina Pedraza; Céline Bolliger; Katrin Scheinemann; Eva Maria Tinner; Eva Bergstraesser; Andre Oscar von Bueren; Gisela Michel (BMC Palliative Care)
Abstract Introduction. The death of a child profoundly impacts parents, often leading to anxiety, depression, and posttraumatic stress. However, factors such as resilience—defined as the capacity to adapt to adversity—are less explored. Resilience may mitigate grief-related distress. This study aimed to: (a) describe and compare resilience levels between bereaved parents and parents of childhood cancer survivors (CCS parents), (b) identify sociodemographic and cancer-related determinants of resilience among bereaved parents, and (c) investigate resilience’s association with psychological distress and prolonged grief disorder. Methods. This is a cross-sectional study done in Switzerland. Bereaved parents were recruited from three hospitals and through patient advocacy groups. CCS parents were taken from a nationwide, population-based study (Swiss Childhood Cancer Survivor Study-Parents). Resilience, psychological distress, and prolonged grief disorder were assessed using the Connor-Davidson Resilience Scale (CD-RISC 10), Brief Symptom Inventory-18 (BSI-18), and Prolonged Grief 13 (PG-13), respectively. Regression analysis (linear and logistic) was used to identify factors associated with resilience, and the association of resilience with psychological distress and prolonged grief disorder (adjusted for age, sex, and time since death). Results. We included 103 bereaved parents and 345 CCS parents in the analysis. Bereaved parents were younger compared to CCS parents (mean 53.7, SD 8.3 vs. 62.5, SD 6.7 years, p < 0.001), with both groups predominantly female (66% and 58%). Bereaved parents reported higher resilience scores than CCS parents (crude mean: 29.8 vs. 27.9; p = 0.005), with adjusted analyses confirming this finding. High risk of poverty was the only significant determinant of lower resilience (adjusted β = -7.37, 95% CI: -11.21, -3.54; p < 0.001). Higher resilience was associated with lower likelihood to report psychological distress (adjusted OR = 0.83, 95% CI: 0.74, 0.93, p = 0.002) and prolonged grief disorder (adjusted OR = 0.73, 95% CI: 0.58, 0.92, p = 0.008). Conclusion. Bereaved parents exhibited higher resilience than CCS parents. Resilience in bereaved parents was strongly associated with reduced psychological distress and lower likelihood of having prolonged grief disorder. Targeting modifiable factors such as poverty may enhance resilience and thereby help to improve mental health outcomes for bereaved parents.